Academy of Language Studies, UiTM Cawangan Perlis successfully organized a workshop on how to present your ideas effectively / Felia Eliesya Fadzil, Nur Hannah Fatini Abd Malek, and Razlina Razali - Fadzil, Felia Eliesya; Abd Malek, Nur Hannah Fatini; Razali, Razlina (2022)
ARAU, June 16, 2022- The Academy of Language Studies, UiTM Cawangan Perlis has successfully organized its second University Social Responsibility (USR) Programme for 2022 by holding the Presenting Your Ideas Effectively Workshop on Thursday.